2022
DOI: 10.1007/s11218-022-09704-8
|View full text |Cite
|
Sign up to set email alerts
|

Number of books at home as an indicator of socioeconomic status: Examining its extensions and their incremental validity for academic achievement

Abstract: The present study investigates the incremental validity of the traditional books-at-home measure and selected extensions (i.e., number of children’s books and number of ebooks) for explaining students’ academic achievement as measured by their academic language comprehension. Using multiple linear regressions, we additionally explore the role of the source of information (i.e., whether information is given by parents or children). Based on cross-sectional data of a German sample of 2353 elementary school child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 60 publications
0
11
0
Order By: Relevance
“…Data on the highest attained maternal education and number of books in the household when the participant was 16 years of age were collected in a background questionnaire, as this information is often used as an easy-to-obtain measure of socioeconomic status (e.g., in the PISA study; Avvisati, 2020) and offers incremental validity over and above other self-report measures (Heppt et al, 2022). These variables were used as proxy measures of socioeconomic status (henceforth SES items; Malanchini et al, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…Data on the highest attained maternal education and number of books in the household when the participant was 16 years of age were collected in a background questionnaire, as this information is often used as an easy-to-obtain measure of socioeconomic status (e.g., in the PISA study; Avvisati, 2020) and offers incremental validity over and above other self-report measures (Heppt et al, 2022). These variables were used as proxy measures of socioeconomic status (henceforth SES items; Malanchini et al, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…It is essential to account for this factor to ensure that the study's findings are not confounded by socioeconomic disparities. One measure that has been often linked to SES is the number of books in the household (Heppt et al., 2022); this has also been used for international large‐scale assessments such as the Progress in International Reading Literacy Study (PIRLS) (Mullis et al., 2019). We adopted this approach, and, in the current study, students provided information about the number of books in the home.…”
Section: Methodsmentioning
confidence: 99%
“…Participants provided several indicators of socioeconomic status (SES), including parental education, parent occupation and number of books in their household (Heppt et al., 2022). Students from different socioeconomic backgrounds may experience varying levels of critical thinking or access to developing this skill.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, as an indicator of ethnicity and culture, native language was measured and 92% of the participants spoke German as their first language. The number of books at home was used as an indicator of socioeconomic status (as is the case with large-scale international assessments of student performance such as TIMSS; see Broer et al, 2019) and 73% of our participants reported to have more than 100 books at home (on a scale from 0: "0 books" to 5: "more than 100 books" (see Heppt et al, 2022).…”
Section: Data Basismentioning
confidence: 99%